The evangelical conversion narrative spiritual autobiography in early modern England - Hindmarsh, D. Bruce; Oxford eBooks (Oxford : Oxford University Press, 2005)
This book traces the rise and progress of 'conversion narrative' in England during the 17th and 18th centuries and establishes some of the cultural conditions that allowed the genre to proliferate.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Evangelical Revival -- Biography -- History and criticism; Christian converts -- England -- Biography -- History and criticism; Autobiography -- Religious aspects -- Christianity -- History -- 18th century; Electronic books